A RECENT REVIEW ON NASAL MICROEMULSION FOR TREATMENT OF CNS DISORDER - L., Jaiswal P.; B., Darekar A.; B., Saudagar R. (International Journal of Current Pharmaceutical Research, 2017)
Nasal route is found to be valuable for targeting drugs to CNS via a different mechanism. The advantages, disadvantages, various aspects of nasal anatomy and physiology, mechanism of drug transport from nose brain, drug selection criteria to cross BBB/Blood-CSF barrier are discussed briefly. Nowadays many drugs have better systemic bioavailability through nasal route as compared to oral administration. In addition, intranasal drug delivery enables dose reduction, rapid attainment of therapeutic blood levels, quicker onset of pharmacological activity, and fewer side effects. There are various approaches in delivering a therapeutic substance to the target site. One such approach is using microemulsion as a carrier for the drug. The main purpose of this study is the use of microemulsion technology in drug targeting to the brain along with mechanism of the nose to brain transport, formulation and formation of the microemulsion and its characterization.